Dividend policy: Reconciling DD with MM☆ - HANDLEY, J (Journal of Financial Economics, 2008)
Miller and Modigliani [1961. Dividend policy, growth and the valuation of shares. Journal of Business 34, 411–433] establish the irrelevance of dividend policy in a perfect capital market. DeAngelo and DeAngelo [2006. The irrelevance of the MM dividend irrelevance theorem. Journal of Financial Economics 79, 293–315.] suggest the Miller-Modigliani analysis is flawed and consequently their central conclusion is incorrect. The purpose of this paper is to show the vital role played by stock repurchases and agency costs in reconciling the two opposing views.